PESAN-PESAN KOMUNIKASI ISLAM DALAM TARIAN TRADISIONAL SEUDATI ACEH - Cut Ayu Mauidhah (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstract: Nowdays, seudati tradisional dancing had Lived aceh province. And about Its origin, it requiremore assessment. Seudati is the most popular and favored traditional dancing By aceh’s people, as specialdancing. The popularity of this traditional dancing had spread troughout Indonesia even abroad. Since thekingdom of aceh, seudati dance is one of traditional dance Which most admired by travelers who comethere. Seudati has sound of music Which been its characteristic, such as sound of music like applause,fingers picking and stomping. The aim of this research is to figure out their values of islamic communicationthat contained in lyrics (verbal) and movements (nonverbal) of seudati dance looked by semiotic perspective.The kind of this research is semiotic analysis by using descriptive-qualitative method of Roland Barthesmodel. The data source of this research consisted of primary and secondary data source, primary datasources are obtained from Aceh seudati file videos Which gotten from agencies of transportation, tourismand social-culture of Lhokseumawe city and secondary data sources are obtained from interviews andliterature books relating to this research.